2013
DOI: 10.1371/journal.pone.0070475
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character in the Child and Adolescent Twin Study in Sweden (CATSS): Comparison to the General Population, and Genetic Structure Analysis

Abstract: BackgroundThe Child and Adolescent Twin Study in Sweden (CATSS) is an on-going, large population-based longitudinal twin study. We aimed (1) to investigate the reliability of two different versions (125-items and 238-items) of Cloninger's Temperament and Character Inventory (TCI) used in the CATSS and the validity of extracting the short version from the long version, (2) to compare these personality dimensions between twins and adolescents from the general population, and (3) to investigate the genetic struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…In relation to these results, large-scale twin studies [12,13] have demonstrated that the temperament dimensions are influenced by environmental factors as well as genetic factors. This phenomenon may be attributable to influence of character on temperament development, i.e., self-concepts may modify the significance and meaning of perceived stimuli, thereby change stimulusresponse characteristics [5].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In relation to these results, large-scale twin studies [12,13] have demonstrated that the temperament dimensions are influenced by environmental factors as well as genetic factors. This phenomenon may be attributable to influence of character on temperament development, i.e., self-concepts may modify the significance and meaning of perceived stimuli, thereby change stimulusresponse characteristics [5].…”
Section: Discussionmentioning
confidence: 94%
“…Last but not least, the association of the self-model with low HA may reflect the goal of the attachment system incorporating the self-model, i.e., to obtain felt security [1,2]. It is noteworthy that the twin studies mentioned earlier [12,13] have shown that genetic factors also influence the character dimensions including SD and C which are strongly correlated with attachment indices as presented here. This finding suggests that attachment styles are formed through interactions of genetic factors and attachment experiences.…”
Section: Self-modelmentioning
confidence: 86%
“…Indeed, among Swedes (Nima, Archer & Garcia, 2012; Nima, Archer & Garcia, 2013), these three strategies (social affiliation, instrumental goal pursuit, and active leisure) have been found to be positively related to subjective well-being. Agency and cooperation are also related to mental health, dysfunction and suffering (Cloninger & Zohar, 2011; Garcia, Anckarsäter & Lundström, 2013; Garcia et al, 2013b; Garcia, Nima & Archer, in press) and are suggested to help the individual become happier and healthier (Cloninger, 2013; see also Johansson et al, 2013, who showed that increases in agency and cooperation are associated to improvement in depression). Moreover, compared to the self-destructives, the self-fulfilling individuals reported more frequently seeking support from faith, performing religious activities, praying, and drinking less alcohol (i.e., the religion happiness-increasing strategy).…”
Section: Discussionmentioning
confidence: 99%
“…According to twin studies, TCI temperament dimensions have shown moderate (RD and persistence) to strong heritability (HA and NS) [15], with RD also sharing some environmental effects [16]. In neurobiological studies trait anxiety, which is characterized by hypervigilance and hyperarousal, can be differentiated from fear, but these two are also overlapping phenomena [17].…”
Section: Introductionmentioning
confidence: 99%